Pioneering Interactive Learning: Enhancing Al-Istima' Skills in 10th Grade Madrasah Aliyah with iSpring Suite 9 Educational Media Development - Nurjanah, Latief; Ridlo, Abdullah (Language, Technology, and Social Media, 2023)
This research aims to develop interactive learning media using iSpring Suite 9 for maharah al-istima’ (listening skill) in class X of Madrasah Aliyah. This learning media is designed to facilitate the teaching and learning process for both teachers and students in maharah al-istima’ subject. The use of interactive learning media with iSpring Suite 9 has significantly increased students' enthusiasm in the learning process and successfully captured their interest in learning. The research follows a development approach based on Sugiyono's model with seven stages, namely potential and problem analysis, data collection, product design, design validation, design revision, product testing, and final product revision. The validation process involved assessments from 2 subject matter experts, 2 design and media experts, as well as feedback from teachers and students. Small-scale testing was conducted with a group of 15 students, followed by field testing involving 42 students of class X at MA Assyifa Karang Sari in South Lampung. The research findings indicate that interactive learning media using iSpring Suite 9 for maharah al-istima’ in class X of Madrasah Aliyah achieved an average percentage of 85% from the assessment by subject matter experts (categorized as highly feasible), 92% from design and media experts' assessment (categorized as highly feasible), 83% from small-scale testing (categorized as very interesting), and 83% from field testing (categorized as very interesting). In conclusion, the utilization of iSpring Suite 9 for interactive learning in maharah al-istima’ subject for class X of Madrasah Aliyah is highly recommended due to its practicality and user-friendly features.